Unraveling Nepal’s Political Turmoil: A Conspiracy Theory Perspective (Research Journal, 2024)
Since the election of 2022 in Nepal, the political landscape has witnessed various political parties engaging in intricate alliances, frequent betrayals, and strategic shifts. The House of Representatives reflects a fragmented environment, with the Nepali Congress as the largest party and the CPN-UML following closely behind, highlighting the challenges of coalition-building in a diverse political landscape. Amidst these dynamics, conspiracy theories have gained prominence as alternative lenses through which observers interpret abrupt political manoeuvres and shifts in power. These theories, sceptical of official narratives, propose hidden agendas, secret deals, or external influences behind political decisions.This article explores the role of conspiracy theories in Nepal’s political discourse, analyzing their emergence and impact post-2022 election. It reviews existing literature on conspiracy theories, emphasizing their appeal in offering simplified explanations for complex political scenarios and their amplification through social media and cognitive biases. The study employs content analysis of media reports and scholarly literature to explore how conspiracy theories manifest within Nepal’s political context, influencing public perception and challenging democratic processes.Key findings highlight the prevalence of opportunism and betrayal in shaping political outcomes, as exemplified by the CPN-Maoist Center’s pivotal switch in alliances from the Nepali Congress to the CPN-UML during government formation. These manoeuvres underscore the pragmatic pursuit of power over ideological consistency, fueling public distrust and raising ethical questions about political conduct. The study calls for enhanced transparency, robust institutional frameworks, and moral leadership to mitigate the negative impact of conspiracy theories on Nepal’s democratic stability.